Effect of Moringa Leaf Extract Addition (Moringa Oleifera Lam.) on Iron and Vitamin C Content and Acceptability of Ledre as an Alternative Snack for Anemia Patients in School Age Children - Rahmat Dyani, Ilham Alfian Rahmat Dyani Alfian (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Anemia is a condition where the hemoglobin level in the blood is lower than the normal value. Normal hemoglobin levels in adolescent females are 12-16 g/dl and adolescent males are 13-17g/dl. One of the causes of anemia can be caused by several factors, namely low intake of iron and other nutrients such as Vitamin A, Vitamin C, Folic Acid, Ribovlafin and Vitamin B12. Ledre is one of the traditional snacks typical of Bojonegoro Regency made from plantain and rice flour. In this study, the product was treated with the addition of moringa leaf extract. This study aims to determine the acceptability and effect of the addition of moringa leaf extract to ledre products on the nutritional content of iron and vitamin C as a snack for people with anemia. The technique of collecting data on the level of favorability test was carried out on untrained panelists totaling 50 people from Bojonegoro Regency. The data were analyzed using Kruskall-Wallis statistical test. Testing the nutrient content of ledre products adding moringa leaf extract in the iron test using the Atomic Absorption Spectrophotometer method. While for vitamin C using titration test. The results of the study of the three formulas showed no significant effect (p>0.05) on the ledre addition of moringa leaf extract at the level of color, aroma, taste, and texture so there was no need for further testing. The test results of iron content in the selected formula, F1, amounted to 1.28 mg/100g. While the vitamin C content in the best formula is F2 amounting to 1.5329 mg/100gram of material.